Решение задачи оптимального планирования выполнения заказов на листопрокатном производстве - Криводубский, О. А.; Косилов, С. А. (НТУ "ХПИ", 2013)
There have been proposed models and methods of decision-making in the planning of the optimal production program for technical systems with a variety of conveyor type heterogeneous manufacturing operations and delay before processing the semi-finished product on the machine. The purpose of planning is to guarantee the fulfillment of the greatest number of orders that meet the technological capabilities of production. Design of the production program is formalized as a problem of optima lplanning. There have been implemented the numerical method for solving this problem and designed the algorithm for solving it.
Keywords: оптимизация; функционал цели; модель математическая; конвейер; алгоритм; обработка заготовок